Real-world clinical utility and impact on clinical decision-making of coronary computed tomography angiography-derived fractional flow reserve: lessons from the ADVANCE Registry. (25th August 2018) - Fairbairn, Timothy A; Nieman, Koen; Akasaka, Takashi; Nørgaard, Bjarne L; Berman, Daniel S; Raff, Gilbert; Hurwitz-Koweek, Lynne M; Pontone, Gianluca; Kawasaki, Tomohiro; Sand, Niels Peter; Jensen, Jesper M; Amano, Tetsuya; et al.
Abstract: Aims: Non-invasive assessment of stable chest pain patients is a critical determinant of resource utilization and clinical outcomes. Increasingly coronary computed tomography angiography (CCTA) with selective CCTA-derived fractional flow reserve (FFRCT ) is being used. The ADVANCE Registry, is a large prospective examination of using a CCTA and FFRCT diagnostic pathway in real-world settings, with the aim of determining the impact of this pathway on decision-making, downstream invasive coronary angiography (ICA), revascularization, and major adverse cardiovascular events (MACE). Methods and results: A total of 5083 patients with symptoms concerning for coronary artery disease (CAD) and atherosclerosis on CCTA were enrolled at 38 international sites from 15 July 2015 to 20 October 2017. Demographics, symptom status, CCTA and FFRCT findings, treatment plans, and 90 days outcomes were recorded. The primary endpoint of reclassification between core lab CCTA alone and CCTA plus FFRCT -based management plans occurred in 66.9% [confidence interval (CI): 64.8–67.6] of patients. Non-obstructive coronary disease was significantly lower in ICA patients with FFRCT ≤0.80 (14.4%) compared to patients with FFRCT >0.80 (43.8%, odds ratio 0.19, CI: 0.15–0.25, P < 0.001). In total, 72.3% of subjects undergoing ICA with FFRCT ≤0.80 were revascularized. No death/myocardial infarction (MI) occurred within 90 days in patients with FFRCT >0.80 ( n = 1529), whereas 19 (0.6%) MACE [hazard ratio (HR) 19.75, CI: 1.19–326, P = 0.0008] and 14 (0.3%) death/MI (HR 14.68, CI 0.88–246, P = 0.039) occurred in subjects with an FFRCT ≤0.80. Conclusions: In a large international multicentre population, FFRCT modified treatment recommendation in two-thirds of subjects as compared to CCTA alone, was associated with less negative ICA, predicted revascularization, and identified subjects at low risk of adverse events through 90 days.